IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA DI KAWASAN TAMAN SARI KOTA SERANG - Zulfa Nur Faiqoh; Nazwa Salsabila; Siti Shania Febriyanti Nur Rahid; Angger Kaesar Galih Prasojo; Septiani Pratiwi (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2024)
Abstract This research examines the implementation of the street vendor management policy. Taman Sari, Serang City. A descriptive qualitative method was used to collect data from the Office of Cooperatives, SMEs, Industry & Trade of Serang City. The findings show the government's efforts in relocating traders to more strategic locations, but there are obstacles such as the lack of facilities and infrastructure and suboptimal location changes. Nonetheless, the majority of merchants follow the government's guidelines because they feel it is beneficial for them. Inter-organizational coordination, effective use of resources, and the ability of implementing agents are key in achieving successful policy implementation. The findings of this study shed light on the difficulties encountered in implementing the street vendor arrangement policy and highlight the necessity of inter-organizational collaboration and effective resource management. In conclusion, to achieve policy objectives effectively, joint efforts from various parties are needed to overcome the obstacles that arise during the implementation process.